Keefektifan Layanan Bimbingan Kelompok Teknik Problem Solving untuk Meningkatkan Kemandirian Belajar dalam Menentukan Karir - Arga Wisnu Wardana; Ulfa Danni Rosada (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
Group guidance services are one way of providing guidance to students who have certain problems in a group. Group tutoring services can be said to be effective if students can understand and follow the guidance optimally so that they can increase learning independence. Problem solving techniques are techniques for handling difficulties faced by each individual to reduce a person's sense of lack of understanding in order to achieve success. This research aims to determine the effectiveness of problem solving technique group guidance services to increase learning independence in determining a career. The type of research used in this research is experimental research with a true experimental research design. The objects in this research are the experimental class and the control class. The sample used in this research was taken randomly as a control group with a total of 7 students and 7 students as a class. Data collection techniques used in this research include interviews and observations. The research data was analyzed using the Independent Sample T-Test and the N-Gain test on the SPSS 23 application. The research showed that the average Pretest was 129.74 and Posttest was 138.5. Based on the results of the research that has been carried out, it can be concluded that the increase in respondents' scores from pretest to posttest, giving treatment can improve the results of respondents' answers, there is an increase in learning independence in determining a career after being given treatment.